Influence of personality, biases on financial risk tolerance among retail investors in India - Aniruddha S Rao; Savitha G Lakkol (Investment Management & Financial Innovations)
Investors’ personality traits and psychological biases play a crucial role in the decision-making process and risk-taking behavior of investors. The emotional and psychological factors impact the decision-making, giving rise to biases. These biases make investors make irrational decisions, which signifies the need for this study. This study aims to assess investors’ personalities using HEXACO model and its interaction with biases and financial risk tolerance. The data of 530 retail investors in India, who had more than 2 years of investing experience in the stock market, were collected. The study considered the HEXACO model since it captures all dimensions of personality that are not considered in the commonly used Big Five Model (BFM). The result of structural equation modeling and mediation analysis shows that the ‘honesty-humility’ trait significantly affects overconfidence bias. The mediation analysis of biases between traits and financial risk tolerance showed complete, partial, and no mediation effect depending on the nature of prejudice. Clear distinction of personality traits into ‘virtue traits’ and ‘character traits’ can be observed. This clear distinction paves the way for employing the HEXACO model in future studies.